Handbook for practical letter writing - Baugh, L. Sue, ....- (Lincolnwood, Ill. : NTC Pub. Group, 1996)
Certain situations in life demand written communication. To express sympathy on the death of a loved one, to inquire about a job, to register an official complaint about a product or a service, to offer a recommendation - all these require that you write a letter. The handbook for practical letter writing by L. Sue Baugh shows you how te write these kinds of letters and many more besides. The handbook for practical letter writing shows you: how to get started and strike the right tone in your letters, what forms to use for business letters and for social letters, how to avoid clichés and sexist language, how te make sure your grammar and punctuation are correct. The second part of the handbook for practical letter writing illustrates dozens of model letters, covering nearly every situation where a letter is appropriate.